THU0313 Antineutrophil Cytoplasmic Autoantibodies (ANCA) Positivity as a Red Flag of Severe Disease in Lupus Nephritis. (23rd January 2014) - Messuti, L.; Gremese, E.; Petricca, L.; Gigante, M. R.; Marino, G.; Nowik, M.; Ferraccioli, G.
Abstract : Background: The presence of vasculitis is a well-documented finding in patients with systemic lupus erythematosus (SLE) but it is not yet clear if antineutrophil cytoplasmic autoantibodies (ANCA) play a pathogenetic role or if their positivity is only an epiphenomenon of ANA positivity. Several studies examined this relationship but there are differences in the results and conclusions, although an association with the renal involvement was described (1 ). Objectives: To evaluate the prevalence of ANCA positivity in a SLE cohort, its association with clinical characteristics and the possible clinical implications of ANCA detection. Methods: We retrospectively evaluated the presence of p- and c-ANCA in a cohort of 223 SLE patients (86.5% female, mean age 42.0±14.5, mean follow-up 5.3±3.6 years) in relationship with clinical manifestations, in particular lupus nephritis. Serum ANCA was measured by enzyme linked immunosorbent assay (ELISA) and positivity was considered as values > 2 standard deviation (SD). Results: 40 out of 223 SLE patients (17.9%) were identified as ANCA-positive (ANCA+). 11/40 (27.5%) ANCA+ patients had a lupus nephritis, 9/40 had a neurological involvement, while the remaining patients had a minor organ involvement, articular, cutaneous, serositic and/or haematologic. No difference was observed in the prevalence of ANCA positivity between patients with lupus nephritis (11/76, 14.5%) and patients with no renal involvement (29/147, 19.7%, p=ns). Six out of the 11 SLE nephritis ANCA+ patients (54.5%) had a p-ANCA specificity, 2 (18.2%) had a c-ANCA specificity and 3 (27.3%) were both p- and c-ANCA positive. Analyzing the 76 patients with renal involvement, we observed that 5/11 patients (45.5%) with ANCA+ lupus nephritis developed chronic renal failure in the follow-up compared to 11/65 (16.9%) with ANCA negative (ANCA-) lupus nephritis (p=0.03). Moreover, 3/11 (27.3%) ANCA+ lupus nephritis developed an end stage renal disease requiring chronic haemodialytic treatment, compared to 3/65 patients (4.6%) with ANCA- lupus nephritis (p=0.03). The median age was 44 years in ANCA+ and 39 in ANCA- SLE nephritis subjects (p=0.02). The ANCA became negative during the follow-up after steroid treatment in all patients. No differences were observed between ANCA+ and ANCA- SLE patients with no renal involvement. Conclusions: Data suggest that the positivity of ANCA do not associate with a more severe disease, but it seems to associate with a worse prognosis of a specific organ involvement. ANCA become negative in the course of the disease, therefore they should be evaluated at the disease onset as predictors of renal damage. References: Sen D, Lupus 2003: 12(9):651-8. Disclosure of Interest: None Declared